In and Out of Privileged and Disadvantaged Neighborhoods in Sweden – On the Importance of Country of Birth - Björn Anders Gustafsson; Torun Österberg (Institute of Labor Economics (IZA), 2023)
Moves into and out of privileged neighborhoods as well as moves into and out of disadvantaged neighborhoods in metropolitan Sweden are studied using register data on all moves by adults that took place between 2004 and 2006. Based on estimated multivariate models, we find that, for all four types of moves, age, education, household income, household composition and its changes, as well as labor market status and its changes, matter. However, in addition, where the person was born can matter, as, with some exceptions, foreign-born people are less likely than natives with the same characteristics to move into a privileged neighborhood. Furthermore, foreign-born are typically less likely than natives with the same characteristics to move out of the metropolitan regions. However, considerable heterogeneity in probabilities to move between those born in different categories of countries is found. Adults born in high-income countries are, in many cases, moving similarly to natives with the same characteristics, while this is typically not found among people born in low-income countries. The latter might be due to fewer assets, lesser social capital, discrimination in the housing market or in housing finance, or by choice.
Keywords: J15; J61; R23; 330; residental mobility; neighbourhoods; immigrants; Sweden